«Tres acres y una vaca» El distribuismo o la radical opción moral de la economía contemporánea: «Three acres and a cow» The distributism or the radical moral choice in contemporary economy - Fernández Riquelme, Sergio (Veritas, 2012)
In the history of ideas we can find an original political-economic doctrine born in England in the early twentieth century known as Distributism, which provided a socio-political settlement profoundly humanist, from the historic renovation of Catholic social teaching in the «Industrial revolution Era». But a doctrine which appears also in the early twentieth century, as a possible interpretive paradigm of the «social Issue» of this new millennium: the integral human development, from the defense of natural communities and the human dignity against the dangers of the «engineering social» proposals and of transnational realities in the global economy.